Do Foreigners Crowd Natives out of STEM Degrees and Occupations? Evidence from the U.S. Immigration Act of 1990 - Tyler Ransom; John V. Winters (Institute for the Study of Labor (IZA), 2016)
This paper examines effects of the U.S. Immigration Act of 1990 on STEM (science, technology, engineering, and mathematics) degree completion and labor market outcomes for native-born Americans. The Act increased the in-flow and stock of foreign STEM workers in the U.S., both by increasing green card allotments and by expanding temporary work visas via the H-1B visa program. These policy changes potentially altered the relative desirability of various college majors and occupations for natives. We examine effects of the policy on STEM degree completion, STEM occupational choice, and employment rates separately for black and white males and females. We identify the effects using variation in natives' exposure to foreign STEM workers and the geographic dispersion in foreign-born STEM workers in 1980, which precedes the Act and predicts future foreign STEM flows. We find that the Immigration Act changed natives' skill investment and utilization in three ways: (1) it pushed black males out of STEM majors; (2) it pushed white male STEM graduates out of STEM occupations; and (3) it pushed white female STEM graduates out of the workforce.
Keywords: J24; J61; 330; immigration; STEM; college major; occupation; crowd out